DR. SEUSS’ SYMBOLS ON KING STILTS TO CHARACTER BUILDING: A MULTIDISCIPLINARY STUDY OF CHILDREN LITERATURE - Rikat Eka Prastyawan; Oikurema Purwanti; Febiola D. Kurnia (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2021)
Symbol is the used object by the author to convey messages in literary works through learning process to get hidden meanings. In children literature, symbols could become objects as the bridge for parents or teachers to be role models to transfer the positive traits for readers especially children as the next generation of a nation. This research aimed to find the symbols on King’s Stilts Children Book referring to character building as nation character traits. A descriptive qualitative was used as a method in this study by using content analysis based on heuristic and retroactive reading referred to checklist of character building assessment to the children book entitled The Kings’ Stilts written by Dr. Seuss, an American author of children literature. The result showed that King Birtram, Eric, and Lord Droon were symbols for signifiers which were used to represent the signified involving the character traits such as self discipline, hard work, responsible, social care, creative, sense of humor, wise, solemn, deceptive, evasive, uncaring, unfeeling even dishonest. It could be concluded that exploring hidden meanings of the used symbols in children literature could become one of the ways to build the positive characters for children even stimulating the reading habit as the implication of this study.